Analisis Performa Protokol LTE untuk Pengiriman Periodic Messages pada Vehicular Network - Ferra Adelinna Wibowo Putri; Adhitya Bhawiyuga; Kasyful Amron (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Long Term Evolution or LTE is a mobile wireless communications technology with downlink data transmission rate of 150 Mbps and 75 Mbps Uplink. Seeing good LTE performance, came the idea to combine LTE as a communication protocol on the vehicular network. Basically the vehicular network already has a de facto communication protocol that is an ad-hoc 802.11p short range communication. However, with close range transmission on the 802.11p protocol there is a problem with the communication between the vehicle and the Road Side Unit or RSU in the delivery of periodic messages on the condition of the vehicle moving at high speed and the RSU is not in a vehicle transmission span. Although LTE comes with non ad-hoc infrastructure but LTE offers wide transmission range and high transmission speed. To see the performance of LTE on the vehicle network then do the research, with traffic scenario closer to reality. Preferred scenarios are traffic scenarios with vehicle density, vehicle speed, transmission data and transmission frequency. The results show that LTE has a good performance to be applied and developed in the vehicle network. By showing a small value less than 500 ms in the graphics increase end-to-end delay and 0 % for packet loss on vehicle speed scenarios and messaging frequency in accordance with the needs of safety applications on the vehicular network.